PENGARUH BUDAYA RELIGIUS TERHADAP AKHLAK SISWA DI MI ROUDLOTUN NASYIIN SINGOSARI MALANG - Tanzilur Rizki Asania; lia Nur Atiqoh Bela Dina; Bagus Cahyanto (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Religious culture is one of the supporters of religious education, because religious culture is an activity that can improve the spirituality of students by creating human beings who have faith, have noble character and fear Allah SWT. This study aims to determine the significant influence of religious culture on the morals of students at MI Roudlotun Nasyiin Singosari Malang. The variables used are religious culture (x) as the independent variable and student morals (y) as the dependent variable. The research was conducted by observing, documenting and distributing questionnaires to 40 students. This research uses a quantitative approach with a descriptive correlative type of research. The data analysis technique used is a simple linear regression test. In analyzing this data, the researcher uses the SPSS type 26 statistical data processing application. Based on the results of the regression test, it shows a significance value of 0.000 > 0.05 probability (5%), then the regression model can be used to predict student character variables or in other words, there is an influence of cultural variables. religious beliefs (x) on student morals (y) at MI Roudlotun Nasyiin. The coefficient of determination test (R square) produces 0.49, which means that the influence of the independent variable (Religious Culture) on the dependent variable (Student Morals) is 49.3%. While the remaining 50.7% is influenced by other factors outside the study. Keywords: Religious culture, Student morals, morals formation